The presence of CSCSs and EMT markers are positively correlated with canine malignant mammary gland tumors in Iran - Marzban, Havva (The Philippine Journal of Veterinary Medicine, 2022)
Canine malignant mammary gland tumors (MMGTs) are one of the most prevalent neoplasia in bitches. Thus, this present work was designed to evaluate the correlation of cancer stem cells (CSCs) existence and epithelial-mesenchymal transition (EMT) phenomena with well-known prognostic factors, including Ki-67, TNM staging that determines tumor size (T), lymph nodes involvement (N) and distant metastases (M) as a whole factor, and tumor infiltrating lymphocytes (TILs) in 25 formalin-fixed paraffin embedded blocks (FFPEBs) of canine MMGTs. FFPEBs were cut, underwent immunohistochemistry staining with primary antibodies including Ki-67, vimentin (as an EMT representative), CD44, CD24, and ALDH1 for detecting CSCs. The Pearson Chi-Square and t tests were applied for finding statistical correlations among variables. Significant correlation was found between presence of CSCs and Ki-67 (P=0.004). Furthermore, a statistically significant correlation was shown between CSCs+/EMT+ cases with Ki-67 (P=0.006). Among three CSC markers, ALDH1 illustrated a positive correlation with EMT (P=0.015). No significant differences were found between presence of TILs and all other investigated variables such as CSCs, EMT, Ki-67, and TNM stages. Thus, for the first time in Iran, results showed the importance of the association between CSCs, EMT, and Ki-67 in relation to the emergence of malignant behavior of canine MMGTs.